The Study of Speech Acts of Joko Widodo’s Speech in Annual Session People’ Consultative Assembly (MPR) 2024 - Tuti; Ilinawati; Dharma, Yokie Prasetya (Fakultas Keguruan dan Ilmu Pendidikan, 2025)
This research examines the application of speech acts in the political language of Indonesian President Joko Widodo (Jokowi), focusing on his 2024 Annual Session address at the People’s Consultative Assembly (MPR) RI. Using a qualitative content analysis approach, the study categorizes different speech acts, including assertive, expressive, directive, commissive, and declarative forms. Jokowi's speech, heavily cantered on assertive acts, emphasizes the significance of presenting factual content to strengthen public trust and highlight governmental achievements. His selective use of expressive acts enables an emotional connection with the audience, fostering solidarity and a shared sense of identity. Importantly, the lack of directive and commissive acts reflects the speech’s retrospective and reflective character, fitting the formal context where reviewing past accomplishments outweighs issuing commands or promises. Through speech act theory, this study explores how Jokowi tactfully combines information with emotion to convey authority, empathy, and stability. The integration of hybrid speech acts, such as assertive-expressive forms, enhances the speech's impact by embedding emotional weight into factual statements, promoting deeper audience engagement. This analysis reveals Jokowi’s ability to use language as both a communication tool and a means to shape public sentiment. The findings offer insight into the essential role of language in political discourse, showing how speech acts can consolidate leadership and unity in structured political environments.